Keya Das's second act : a novel - Deb, Sopan (Simon & Schuster, 2022)
"From a New York Times reporter and memoirist Sopan Deb comes a heartwarming and charmingly funny debut novel about a box in the attic that leads one Bengali-American family down a path toward rediscovering family love, even when splintered. Shantanu Das is living in the shadows of his past. In his 60s, he finds himself iced out of his traditional Bengali community after an uncouth divorce from his wife, Chaitali; he hasn't spoken to his eldest daughter Mitali in months; and most painfully, he lives each day with the regret that the Dases couldn't accept their youngest daughter Keya after coming out as gay. As the anniversary of Keya's death approaches, Shantanu wakes up one morning utterly alone in his suburban New Jersey home and realizes it's finally time to sell the place. That's when he discovers a tucked away box in his attic that could change everything. When Mitali Das gets a call from her estranged father asking her to come back to New Jersey and help him pack up the house, she does so out of pity. But then father and daughter find the manuscript of an unfinished play Keya and her girlfriend had been writing. It's a wild idea, but Shantanu has nothing left to lose: what if they were to stage the play? It could be an homage to Keya's memory, and a way to make amends. But first he'll need to convince Keya's girlfriend, Pamela, to give her blessing. Soon Shantanu has assembled a host of unlikely helpers-Kalpana, his traditional Bengali mother; Catherine, his dry witted girlfriend; his ex-wife Chaitali and her new husband, Jahar; and Neesh, Mitali's boyfriend who, with surprising revelations from his past, binds them all together. Set in the vibrant world of the Bengali New Jersey suburbs, Keya Das's Second Act is a warmly drawn homage to family, creativity, and second chances. In his debut novel, Sopan Deb has written a poignant and at turns surprisingly hilarious testament to the unexpected ways we build family and find love, old and new"--